Bariatric Therapy Alliance between Gastroenterologists and Surgeons - Mathus-Vliegen, Elisabeth M.H (Springer International Publishing, 2018)
This book aims to deepen collaboration between gastroenterologists and surgeons by providing endoscopists and gastroenterologists with a clear understanding of the anatomic alterations likely to be observed after bariatric surgery and acquainting bariatric surgeons with the possibilities offered by endoscopic treatment of obesity itself and of the complications associated with bariatric surgery. The treatment approach in patients with obesity and morbid obesity is usually stepwise, starting with dietary measures, exercise, and behavioral therapy, followed by pharmaceutical therapies, endoscopic bariatric therapy, and, finally, bariatric surgery. Endoscopists and gastroenterologists are involved first because the gastrointestinal tract is affected by obesity-related co-morbidity and second because it provides access for a range of treatment modalities involving endoscopy. Bariatric surgeons may need the assistance of endoscopists and gastroenterologists in the preoperative work-up of patients, in the perioperative period, when acute complications may require an endoscopic intervention, or in the late follow-up period, when complications or insufficient weight loss may be present. This book will be of value for both groups of specialists, enabling them to optimize their cooperation to the benefit of patients.